Effectiveness of Performance of Prosecutor's Office in Preventing Corruption Crime after the Team's Disbandment - Joko Kris Sriyanto; Bambang Tri Bawono (Law Development Journal, 2021)
The objectives of this study are: 1. To find out and analyze the effectiveness of performance of Grobogan District Attorney in the context of preventing criminal acts of corruption after the dissolution of Regional Government and Regional Development Guards and Security Team (TP4D) in the construction of legal system. 2. To find out and analyze the obstacles faced by the Grobogan District Attorney in the context of preventing criminal acts of corruption after the dissolution of Regional Government and Regional Development Guards and Security Team (TP4D) and their solutions. The research method used is juridical sociology, which is an approach that studies social phenomena in society with legal aspects. Based on the research, it is concluded that as the implementation of duties of Guards Team, Government Security and Regional Development (TP4D), the Grobogan District Prosecutor's Office remains professional in carrying out its duties in the context of preventing criminal acts of corruption after the dissolution of guard and security team for government and regional development (TP4D) in the construction of a legal system that is right. in a period of 3 (three) years, starting in 2016, 2017, 2018 and 2019, the Team of Guards, Safeguards for Government and Regional Development (TP4D) of Grobogan District Prosecutor's Office has handled corruption crimes, showing an achievement from one of roles. The Attorney General's Office in optimizing the prevention of criminal acts of corruption through the Regional Government and Development Guard and Security Team (TP4D).